EFL classroom learning environment at a Thai university: What variables matter for low-proficiency students? - Budi Waluyo; Safnil Arsyad (JOALL (Journal of Applied Linguistics and Literature), 2022)
This study investigated the EFL classroom learning environment at a university in Thailand from the perspective of low-English proficiency students. Using structural equation modelling, five hypotheses involving variables generated by students and teachers were investigated (SEM). According to the findings, task orientation in low-proficiency students was the key to boosting students' English course grades. In the case of low-proficiency students, equity, teacher support, and student cooperation were not found to be important. Student cohesion was also found to be an unreliable predictor of students' English grades. Because research on the classroom learning environment engaging low students is still limited, these findings suggest future investigation.